2013
DOI: 10.4103/0976-0105.109404
|View full text |Cite
|
Sign up to set email alerts
|

Study of pharmacological activities of methanol extract of Jatropha gossypifolia fruits

Abstract: Objective:The present study was carried out to investigate the possible in vivo analgesic, neuropharmacological and anti-diarrheal activities of the methanol extract of Jatropha gossypifolia fruits.Materials and Methods:The analgesic activity was measured by acetic acid induced writhing inhibition test. The neuropharmacological activities were evaluated by hole cross, hole-board, and elevated plus-maze (EPM) tests and the anti-diarrheal activity was assessed by castor oil induced diarrhea inhibition method.Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…In hole board test, the extract showed highly significant anxiolytic activity at a dose of 200 mg/kg, whereas the same activity was observed at 400 mg/kg dose in elevated plus-maze test [111]. Similar results were observed in the methanolic extract from fruits [110]. …”
Section: Pharmacological Activitiesmentioning
confidence: 67%
“…In hole board test, the extract showed highly significant anxiolytic activity at a dose of 200 mg/kg, whereas the same activity was observed at 400 mg/kg dose in elevated plus-maze test [111]. Similar results were observed in the methanolic extract from fruits [110]. …”
Section: Pharmacological Activitiesmentioning
confidence: 67%
“…The fruit is capsular, with three furrows, containing a dark seed with black spots (Félix-Silva et al, 2014). Regarding its phytochemical constitution, alkaloid, steroids, saponin, lignan, tannin, phenolic compounds, flavonoid, curcin, triterpenes, diterpene, jatrophone, jatropholones A and B, jatrophatrione, apigenin, and cyclogossine A have been reported in different extracts from different parts of this plant (Apu et al, 2013;Félix-Silva et al, 2014;Khyade, Vaikos, 2011;Saini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In several studies compounds from plants have been shown to have anxiolytic activity (Gadekar, Sourabh, & Jitender, ; Herrera‐Ruiz, Román‐Ramos, Zamilpa, Tortoriello, & Jiménez‐Ferrer, ; Sandeep & Suresh, ). Their anxiolytic effect has been attributed to its effect on gamma‐amino‐butyric‐acid (GABA), receptors in the CNS (Apu, Hossain, Rizwan, Bhuyan, & Jamaluddin, ) which may be the mechanism through which stigmasterol acts. This study provides experimental/scientific support for the folklore use of G. carpinifolia in the management of anxiety.…”
Section: Discussionmentioning
confidence: 99%